CAPITAL BUDGETING ANALYSIS OF THE FEASIBILITY OF FIXED ASSETS INVESTMENT IN PT ALINCO - Murdiansyah, Isnan; Munir, Misbahul; Putra, Yuniarti Hidayah Suyoso; Slamet, Slamet (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to determine and assess the feasibility of investing in replacing and adding machines at PT. Alinco. Based on the calculation results of the investment feasibility assessment, namely, 1). The payback period value of the old investment is 2 years 6 months, longer than the value of the new investment, namely 1 year 9 months. This shows that new investments are more feasible because the return on investment is faster than investments in old assets. 2). Net Present Value of new investment worth Rp. 102,886,168, greater than the Net Present Value of the old asset investment worth only Rp. 59,096,534, which means that looking at the NPV value itself, the NPV of the new investment is greater than the NPV of the old investment because it has a different rate of return, the return rate for investing in new assets is 32%, while for investing in old assets the rate of return is 32%. return is only 18%. In conclusion, the value of new investments is more feasible than investments in old assets. 3). The Profitability Index (PI) for investment in old assets is only 1.1 and the Profitability Index for investment in new assets is 1.3. By comparing the present value of cash flow with the investment value and calculating the present value of cash flow for each investment using a different rate of return, so that from this it can be concluded that the PI on new investments is more feasible with a greater rate of return than PI on old investments that produce a smaller rate of return. So overall, from the calculation results of the investment feasibility assessment, a final conclusion can be drawn that the new investment to be made by the company is worthy of replacing the old investment.